Non-integer (non-harmonic) spectral analysis of a Drought index for the American great plains - OLADIPO, E. OLUKA YODE (MAUSAM, 1989)
A non-integer (non-harmonic) spectral analysis approa.ch is presented and used to search for periodicities in the drought indices for the Interior Plains, of North America, Covering a period of at lest 70 years. Power spectrum analysis of the drought Indices series revealed that the quasi-biennial and quasi-triennial are common periodicities in the drought series for many stations. The drought spectrum is also dominated by peaks with periods of about 5-6 years. These significant periodicities in the 2-6 year wave bands are sporadic in spatial occurrence; they can be evident at one place while being absent at another a few hundred kilometers away